Penerpan Metode Arrasyid dalam Meningkatkan Pemahaman Bahasa Arab di Era Digitalisasi Siswa Kelas X SMA IT Daarul Hikmah Boarding School Bontang Tahun Pelajaran 2023/2024 - Abror, Ahmad Sidik; Husain, Ahmadi (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This study aims to determine the effectiveness of the Ar-Rasyid method in improving Arabic language comprehension in the digital era for grade X students of SMA IT DHBS. The research method used is qualitative with data collection through observation, interviews, and documentation. The results of the study indicate that the Ar-Rasyid method is able to significantly improve students' understanding of the basic rules of nahwu science. The structured approach of this method, which combines memorization with songs and practice, has proven effective in improving students' Arabic language skills. This study also highlights the importance of digital tools and resources in supporting the Ar-Rasyid method, creating a more engaging learning environment. Overall, this study shows that the Ar-Rasyid method is effective in improving Arabic language comprehension in the digital era, with improved students' abilities in translating verses of the Qur'an, reading, and writing in Arabic. However, the study notes that the application of this method requires more in-depth explanation and correct sequence, especially for students without a background in Arabic.